Extent and architecture of major fault systems between northern Victoria Land and the eastern margin of the Wilkes Subglacial Basin (East Antarctica) - ARMADILLO, EGIDIO; BALBI, PIETRO; Ferraccioli, F; Bozzo, E. (2013)
Terrane bounding and intra-terrane faults of the Ross Orogen in East Antarctica are linked to several phases of Cambrian to Ordovician age subduction and accretion along the active paleo-Pacific margin of Gondwana. Here we compile and analyse new enhanced aeromagnetic anomaly images over the Northern Victoria Land (NVL) segment of the Ross Orogen and the eastern margin of the Wilkes Subglacial Basin (WSB) that help constrain the extent and structural architecture of these fault systems and enable us re-assess their tectonic evolution. Long-wavelength magnetic lows and residual Bouguer gravity highs are modelled as several-km thick inverted sedimentary basins of early Cambrian(?) age. Tectonic inversion occurred along major thrust faults during the late stages of the Ross Orogen, forming a major high-grade pop-up structure within the central Wilson Terrane, flanked by lower grade rocks. The Prince Albert Fault System can now be recongnised as being located to the west of the Exiles Thrust fault system rather than representing its southern continuation. Relatively thin sheets of mylonitic sheared granitoids and possible ultramafic lenses are associated with the late-Ross (ca 480 Ma) Exiles Thrust fault system, while significantly larger and thicker batholiths were emplaced along the Prince Albert Fault System. Recent zircon U-Pb dating over small exposures of gabbro-diorites within the Prince Albert Mountains to the south lead us to propose that this part of the magmatic arc was emplaced during an earlier phase of subduction (~520 Ma or older?), compared to the late-Ross intrusions to the east. Whether the Prince Albert Fault System was indeed a major cryptic suture in early Cambrian times (Ferraccioli et al., 2002, GRL) remains speculative, but possible. Our aeromagnetic interpretation leads us to conclude that these inherited terrane bounding and intra-terrane fault systems of the Ross Orogen exerted a key influence on Cenozoic tectonic blocks and faults of the Transantarctic Mountains, and that the eastern ...